Implementasi Program Halaqah Terhadap Peningkatan Keterampilan Tartilul Qur’an di MAS Tihamah Putri - Rima Nurmala; Jajat Darojat (PT. Pusmedia Group Indonesia, 2023)
The focus of this research is the implementation of the Qur'anic halaqoh program at MAS Tihamah Putri during the 2022/2023 academic year. The main goal of religious (Islamic) education is student diversity, not just religious understanding, which is the center of the study. In other words, religious (Islamic) education prioritizes being (religion or life) over just knowing (knowing religious teachings and values) or doing (being able to do what is known) after being taught at school. Islamic education focuses more on morals, students not only learn the language, but also have the desire and habit to apply religious teachings and values in daily life. The purpose of this study is to determine whether the halaqoh program affects students' Tartilul Qur'an skills at MAS Tihamah Putri in the 2022/2023 academic year. This study used a qualitative descriptive approach. The purpose of this study was to collect data about the implementation of the halaqoh program at MAS Tihamah Putri. Data about the halaqoh program were collected through observation, interviews, and documentation. The study involved teachers, students, and the principal. Furthermore, the results of data collection will be tested for data validity and analyzed starting from data collection, reduction, data presentation and conclusion drawing. The results of this study can be concluded that this halaqoh program is quite effective in improving Tartilul Qur'an skills at Madrasah Aliyah Tihamah Putri. This halaqoh program is expected to provide added value for students in madrasah. With this program, it is expected that students will be better and istiqomah in reading the Qur'an. Keywords: Halaqah Program; Skills Enhancement; Tartilul Qur'an.